Leveraging Major Event Legacy: Community Sport Clubs in Aotearoa New Zealand. - Campbell, Amber (Auckland University of Technology, 2023)
Major sport event (MSE) proponents have consistently promised that hosting a MSE will leave a sport participation legacy as by-product of hosting (Grix & Carmichael, 2012; Weed et al., 2015; Wicker & Sotiriadou, 2013). Yet, there is limited evidence that this is true (Hindson et al., 1994; Thomson et al., 2020; Weed et al., 2015). It is argued that if a MSE is leveraged, there is potential for a sport participation legacy (Chalip et al., 2017). A key stakeholder vital to leveraging a MSE are community sport organisation’s (CSOs), who are the point of entry for communities to engage with organised sport (Doherty & Misener, 2009; Misener et al., 2015). However, there is limited research on a CSO’s ability to leverage a female-specific major sport event (Achu et al., 2022; Dickson et al., 2020). This research asks, “To what extent will the leveraging of legacy-related experiences of New Zealand-based community sport administrators differ over the duration of a major event’s lifecycle (pre, during, post)?”. Three sub questions were also implemented to aid the study 1). What are the pre-event leveraging of legacy-related experiences of community sport administrators, regarding the World Cups being hosted in New Zealand 2022 and 2023? 2). What were the experiences of community sport administrators, regarding the leveraging of legacies offered during the World Cups being hosted in New Zealand in 2022 and 2023? 3). What is the role of organisational capacity of community sport administrators within the leveraging of legacies of major women sport events? To address the research questions an explanatory mixed methods approach was undertaken. A survey was sent out with the National Sport Club Survey to cricket, rugby and football community clubs in New Zealand. Afterwards six interviews were completed, and a collection of Facebook posts, and website screenshots were taken of cricket, rugby and football community sport clubs. A key finding was that CSO’s do not have the pre-requisite organisational capacity necessary to successfully leverage a major sport event to increase participation. Therefore, organisational capacity is the strongest determinant in a CSO’s ability to leverage a major sport event for a sport participation legacy. Consistent across the survey, interviews and content analysis was that the CSO’s in this study identified that their national sport organisation (NSO) did not support them in their endeavours to leverage with a distinct emphasis on poor communication between NSO’s and CSO’s. The findings also reflect how important the tangibility of a MSE is to a CSO, and the identification tangible and intangible legacies considered to be most important to CSO’s when leveraging a MSE. These findings identify the core challenges facing CSO’s in their attempts to leverage MSE’s for an increase in participation. Particularly, these findings provide understanding for NSO’s, RSO’s and CSO’s on the issues impeding a successful participation legacy through leveraging. Critically, for future MSE’s held in New Zealand, the findings provide evidence of what needs to be done to secure a successful participation legacy.